2017
DOI: 10.1111/1556-4029.13490
|View full text |Cite
|
Sign up to set email alerts
|

Human Electrical Muscular Incapacitation and Effects on QTc Interval

Abstract: Human Electrical Muscular Incapacitation (HEMI) is used to subdue combative individuals. Changes in cardiac electrical activity have been proposed as the cause of death in a small fraction of these individuals. The current study sought to determine whether changes in QTc interval occur after HEMI exposure. Twenty-four participants had EKG readings before a 5-second HEMI exposure and within 30 min after exposure. All subject EKGs were read by a data-blinded cardiac electrophysiologist who calculated a QT correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Independently of the general quality of the included studies, findings were categorized based on the possible risk of methodologic bias (Table 1 and Table 2). Table 1 presents information on the 11 included studies that were found to have a lower possible risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Independently of the general quality of the included studies, findings were categorized based on the possible risk of methodologic bias (Table 1 and Table 2). Table 1 presents information on the 11 included studies that were found to have a lower possible risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…25 Moreover, the QTc interval is still mainly used to analyse the risk of arrhythmia associated with specific drugs or procedures. 26,27 Second, the small sample size of this study could be a limitation. However, the post-hoc power analysis showed a power of 0.987 when using the mean value of the QTc interval before anaesthetic induction and 90 minutes after pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 97%
“…Drs. Luceri, Kroll, Calkins, and Halperin pose many questions about the present paper . Several of these questions were answered in the reply to Drs.…”
Section: Descriptive Statistics and Inferential Test Of Means For Thementioning
confidence: 92%